Treatment of severe recalcitrant pyoderma gangrenosum with ustekinumab. (4th December 2017) - Low, Zhi Mei; Mar, Adrian
Abstract: An increased expression of interleukin‐23 has been observed in patients with pyoderma gangrenosum, leading to the use of ustekinumab as a therapeutic option. We report the successful use of ustekinumab in three patients with treatment‐resistant pyoderma gangrenosum of varying clinical presentations.